Halalan toyyiban concept in the broiler chicken farms in Subang, West Java, Indonesia: a perspective on current operational practices - Aufar, Muhammad Haikal; Abd Wahab, Amelia Yuliana; Al-Saari, Nurhidayu (AIJR Publisher, 2023)
This research focuses on exploring the operational practices related to the halalan toyyiban concept at broiler chicken farms in Subang, West Java, Indonesia. The study examines the current practices at the farm, emphasizing the importance of using halal and toyyiban feed components and following appropriate operational procedures to maintain the health and hygiene of the broiler chickens. It also highlights the issue of some breeders or companies using prohibited ingredients, which can have negative consequences for consumers. The research aims to answer four main research questions: (1) Definition of al-Jallalah in broiler chickens; (2) Current operational practices at broiler chicken farms in Subang including the systems, feed ingredients, and common practices used in feeding broiler chickens; and (3) Understanding of halalan toyyiban concepts among farm employees and their incorporation into daily procedures. The study employs content and comparative analysis methods, utilizing qualitative research. The findings revealed a lack of awareness among breeders regarding the importance of prioritizing halal and toyyib in their operational practices, to produce safe and high-quality chicken for consumption.